Health risk assessment of heavy metals via dietary intake of foodstuffs from the Multan, Pakistan - Atif Amin, Baig; Muhammad, Ibrahim; Muhammad, Afzaal (2019)
Naturally occurring heavy metals are becoming concentrated as a result of human activities such as factory wastes, chemicals releasing from the automobiles, and several other sources toxic to human. These activities posed heavy metal pollution to irrigated water, soil, and vegetables. These metals are not digested into human body and stores in the body tissues leading to the metabolic disorders through the food chain. To assess these health risks, it is essential to quantify the heavy metals in the vegetables. This study was conducted to investigate heavy metals (Zn, Ca, and Mg) concentrations in different parts (roots, stems, leaves, and fruits) of tomato plant (Lycopersicon esculentum), sampled from three different locations of Multan district. Roots, leaves, stems, and fruits were oven dried at 110˚C and 2 g of each sample was digested with 5 ml of concentrated nitric acid (Merck). These samples were then subjected to atomic absorption spectrometry (Hitachi Model A-1800) for analysis of these metals. The results of this study revealed that the concentration of metals in L. esculentum increased in the order of Ca > Mg > Zn. By the comparison of all three metals accumulated in different parts of L. esculentum, we concluded that Ca and Mg are present in higher concentration with the exception of zinc which has rather low toxicity but a severe impact on human health. Results of our scenario show that HRI value for Zn is greater than 1 so it poses potential risks to human health.